ANALYSIS AND OPTIMATION OF COOLING TOWER GEOTHERMAL POWER PLANT UNIT 4 CASE STUDY PT. PERTAMINA GEOTHERMAL ENERGY KAMOJANG AREA - ABIMOTO (NIM : 13107043); Pembimbing Utama : Dr. Ir. Ari Darmawan Pasek, AZFAR
PT. Pertamina Geothermal Energy (PGE) is one of the multinational company that operates in renewable energy sector. Based on one of the ongoing program called CIP (Continuous Improving Program), PT. Pertamina is planning to optimize all of the system and performance in the power plant. One of the main factor affecting the power plant efficiency is the performance of the cooling tower. It is considered as one of the main factor because in the end the temperature of water leaving the cooling tower affects the performance of the condensor. Condensor needs a cold temperature of water from the cooling tower to achieve a good vacuum pressure. The purpose of this research is to get an optimal condition for the operation in the cooling tower dan to get a cold water temperature as low and as close as posibble to the wet bulb temperaure. Load variation on the fan for every ambient condition is one of the method used to get a better cooling tower effectiveness. An analysis of filler will be done to get a filler type that is suitable for the operation condition in the cooling tower. Simulation by using a software called FLUENT will be done to analyze water flow distribution through the pipe before and after modification that is done by making variations on opening valve to get a uniform distribution water flow on each pipe. The conclusion of this research is that by doing variations of load on the fan, cooling tower effectiveness will increase by 2% - 3%. Analysis of the filler concludes that existing film filler is still the most appropriate filler to be used in cooling towers at PT. Pertamina Geothermal Energy Unit 4 Kamojang due to its value of mass flow rate of water and air is as much as 0,913. By making a variation on opening valve for each pipe leading to the cooling towers, a more uniform distribution water flow will be achieved, approximately 2,3 m/s for each pipe.